Die Chronostratigraphie des Letzt-Glazialen Zyklus aufgezeichnet in Löss-Paläobodensequenzen aus West und Zentral-Europa : The chronostratigraphy of the last glacial cycle recorded in loess-palaeosol sequences from Western and Central Europe - Zens, Jörg (RWTH Aachen University, 2017)
Rheinisch-Westfälische Technische Hochschule Aachen, Diss., 2017; Aachen, 1 Online-Ressource (XI Seiten, Seite 12-220) : Illustrationen, Diagramme, Karten (2017). = Rheinisch-Westfälische Technische Hochschule Aachen, Diss., 2017 : Loess-palaeosol sequences (LPS) are valuable terrestrial archives for the reconstruction of past environmental and climatic conditions especially on a regional scale. The Western and Central European subregions of the European loess belt are characterised by thick and richly structured, but discontinuous sequences. Unconformities are common features and impede the inter-site and supraregional comparison as well as the construction of comprehensive (chrono-) stratigraphic models. Hence, the inclusion of more reliable numerical age information for the sediments holds great potential to increase our understanding of past climate condition and changes.The majority of the available luminescence age from LPS show shortcomings in accuracy and precision compared to luminescence ages obtained from modern optical stimulated luminescence (OSL) methods. Because reliable OSL data is still only available for a small number of LPS many chronostratigraphies still rely on data produced under outdated standards. This implicates a higher temporal uncertainty and challenge every proxy data based correlation to other archives of climatic changes. The main objective of this thesis is to improve the chronological knowledge of LPS by comparative OSL dating on quartz and feldspar. A total number of 46 ages were generated from loess sections from eastern Belgium (Romont), the Lower Rhine Embayment (Garzweiler), the Lower/Middle Rhine transition (Ringen) and the Kraichgau (Frankenbach). The results are not sensitive to the choice of which mineral is analysed and verified the reliability of the established chronologies. However, feldspar minerals embedded in reworked soil sediments are prone to incomplete bleaching during high-magnitude low-frequency erosive processes. This is reasoned by the lower bleachability rate. This leads to age overestimation which makes their usage to construct chronologies challenging. A part of the OSL data was included in a dataset of OSL ages compiled from multiple LPS to calculate the age of the Eltville Tephra (ET) by Bayesian age modelling. The modelling results show a precise and reproducible age, in contrast to the scatter of individual ages from the same stratigraphic position. For the first time it was possible to show a connection between LPS and the Eifel Laminated Maar Archive (ELSA) by the temporal accordance between the ET age and a distinct peak in the volcanic mineral content of the Dehner dry maar. By integrating the volcanic mineral content into the stratigraphic model, the ET age was refined to ± 24.2 ka (previous, ~24-20 ka). It appears that the widely distributed ET is only preserved as cryptotephra within the Eifel maars, which may have been caused by a rapid uplift of the ash associated with a storm moving in westerly direction. By means of OSL ages as well as stratigraphic evidence and grain size data, a composite profile was generated and compared to reference loess records for specific sediment sequences with reliable OSL chronologies. It allows for a refinement of the chronostratigraphy of the recently published lithostratigraphic schemes from Northern France, Belgium, the Lower Rhine Embayment and Central Europe, which inhere weak numerical age control. The integration of Greenland ice core data and the ELSA Stacks into the composite profile enabled to develop a proxy data based event-stratigraphy supplementing previous attempts. The integrated stratigraphical model reveals, with reservation, similar proxy data patterns between the individual records. The compiled OSL chronologies shows a temporal correspondence between climate warming signals recorded in Greenland ice cores and palaeosols in Europe. However, there is no indication that every soil formation is connected to a single Greenland interstadial (GI), but rather to a bundle of GIs. In addition, the duration and magnitude of temperature change of GIs are not indicative for the type and intensity of soil formation. Increasing dust influx into Greenland recorded in ice cores and the higher aeolian activity in Europe inferred by loess sedimentation and/or coarser grain sizes was very likely caused by large-scale atmospheric circulation patterns dominating both regions. The main phases can be identified during the second half of the Lower Pleniglacial (LPG), the Heinrich events 4 and 3, and the Greenland stadial-2 (GS). The high loess accumulation rates during the second half of the Upper Pleniglacial (UPGb) in front of the European Low Mountains seems to be decoupled from the atmospheric circulation patterns controlling the dust influx to Greenland. Proxy data from the Dehner dry maar and climate modelling indicate increasing easterly winds likely caused by persistent high-pressure systems situated above the Scandinavian Ice Sheet. The integration of the ELSA Stacks reveals a coupling with sedimentary successions in loess. The specific palaeosols (tundra gleys, boreal and arctic brown soils) correlate with the landscape evolution zones defined from the ELSA Stacks. Phases of frequent flood layer occurrence corresponds with unconformities in LPS. They are likely caused by a low vegetation coverage during a climate deterioration towards more cold and humid conditions. The flood cluster after the two main pedogenetic phases of the Middle Pleniglacial, the early stage of the UPG and the UPGa/b boundary is responsible for the lack of important stratigraphic information in most LPS from Europe, especially in the Lower Rhine Embayment. Here the sensitivity of the flat topography to extensive erosion is reflected by the low number of in-situ Upper Palaeolithic findings (Aurignacien and Gravettien) and high find concentrations in reworked sediments (in particular in the Kesselt Layer). : Published by Aachen